Sec16 Determines the Size and Functioning of the Golgi in the Protist Parasite, Trypanosoma brucei. (4th April 2014) - Sealey‐Cardona, Marco; Schmidt, Katy; Demmel, Lars; Hirschmugl, Tatjana; Gesell, Tanja; Dong, Gang; Warren, Graham
Abstract The Sec16 homologue in Trypanosoma brucei has been identified and characterized. TbSec16 colocalizes with COPII components at the single endoplasmic reticulum exit site (ERES), which is next to the single Golgi stack in the insect (procyclic) form of this organism. Depletion of TbSec16 reduces the size of the ERES and the Golgi, and slows growth and transport of a secretory marker to the cell surface; conversely, overexpression of TbSec16 increases the size of the ERES and Golgi but has no effect on growth or secretion. Together these data suggest that TbSec16 regulates the size of the ERES and Golgi and this size is set for optimal growth of the organism. <inline-graphic xlink:href="ark:/27927/pgh4dd40" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />